Semi-Automatic Pneumatic Actuated Otak-otak Pin Insertion Machine - Sulaiman, Junaidah; Shaari, Muhammad Farid; Mahmood, Salwa (Progress in Engineering Application and Technology, 2022)
The demand for popular food in Johor, otak-otak, is increasing when it is served as an appetizer in almost all eateries and restaurants. The process of pinning bamboo skewers to attach nipah leaves is done manually by workers which is time-consuming and create a bottleneck in the production. The bottleneck exposed the unwrapped fish paste to the environment which can cause contamination. This research objectives are to determine the concept of otak-otak machine mechanism and to design and simulate the machine prototype with the holder and pin inserter to pin the wrapped otak-otak at both ends simultaneously. This study focused on otak-otak that use nipah leaves and bamboo skewers as its wrapper. Three prototype models were designed in SolidWorks software. The finite element analysis (FEA) method was used to analyse the model structures and simulate the function of the pin insertion mechanism. Based on the result through static analysis, the prototype could withstand the input pressure of 0.2 MPa that was used to operate the machine. However, a displacement of 0.0128 mm (12.8 µ) on the structure indicates that the machine will be affected by vibration throughout its operation.